Simplified Method of Determining Torsional Stability of the Multi-Storey Reinforced Concrete Buildings - Prashidha Khatiwada; Elisa Lumantarna (CivilEng, 2021)
This article proposes a simplified method for determining the elastic radius ratio of the multi-storey reinforced concrete building. The elastic radius ratio is the benchmark parameter of the buildings in determining torsional stability during an earthquake. When buildings are torsionally flexible, the torsional component of seismic response amplifies the overall response of the building. Because of the numbers of simplified assumptions such as the adoption of the single-storey model, much of the published articles have a very limited range of application. Quantifying the interaction of different forces in multi-story non-proportional buildings has been the main challenge of these studies. The proposed “shear and bending combination method” solves this by introducing parameters that can determine the relative influence of individual actions. Moreover, the proposed method applies to buildings with all type of structural systems, having asymmetry, and accidental eccentricity. The method is validated through a parametric study consisting of eighty-one building models and using computer analysis. The proposed method and the research findings of this study are useful in determining the torsional stability of the building, in verifying the results of the computer-based analysis, and in optimizing the structural system in the buildings.